Traditional medicine in Sakarya province (Turkey)and antimicrobial activities of selected species - Uzuna, E.; Sariyara, G.; Adsersen, A.; Karakoc, B.; Otik, G.; Oktayoglu, E.; Pirildara, S.
Traditional medicine in North-West of Turkey (Sakarya province)were studied during a 2 months field study by interviewing local informants from several villages. Plant species used to treat infections were tested for antimicrobial activity. Information was collected for 46 plant species from 30 families and for 5 animal species. Twenty four of the plant species were cultivated. Most used families were Asteraceae, Cucurbitaceae, Lamiaceae and Rosaceae and the most used plants were Artemisia absinthium, Equisetum telmateia, Lavandula stoechas, Melissa officinalis, Tussilago farfara and Urtica dioica. A total of 139 medicinal uses were obtained. Plants are used mainly for infectious diseases (18
Keywords: TRADITIONAL MEDICINE; SAKARYA; NORTH-WEST ANATOLIA (TURKEY); ANTIMICROBIAL ACTIVITY